2016
DOI: 10.1002/jcb.25641
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Hairless Protein as a DNA Binding Phosphoprotein

Abstract: The mammalian hairless (Hr) protein plays critical roles in skin and brain tissues, but how it interacts with DNA and partner protein is only now being defined. Our initial tests of four consensus response elements, revealed that rat Hr can specifically bind to a consensus p53 response element (p53RE), 5'-AGACATGCCTAGACATGCCT-3', but not to response elements for NF-κB, TCF4 or Sp1. We then employed ChIP assays which verified that human HR binds to a p53RE of the GADD45A gene in both HEK293 (embryonic kidney) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…We recently demonstrated that rat Hr is a specific substrate for protein kinase C using an in vitro phosphorylation assay. We further showed using mass spectrometry that human HR is phosphorylated in intact human U87 glioblastoma cells at Ser‐416, located in a highly conserved region which partially fulfills the criteria of a PKC site [Brook et al, ]. The previously published studies by Yang et al [] utilizing human skin fibroblasts also reported this same phosphorylation site, while also revealing an additional phosphorylation site at Ser‐425.…”
Section: Hr Structure/function Studiesmentioning
confidence: 73%
See 2 more Smart Citations
“…We recently demonstrated that rat Hr is a specific substrate for protein kinase C using an in vitro phosphorylation assay. We further showed using mass spectrometry that human HR is phosphorylated in intact human U87 glioblastoma cells at Ser‐416, located in a highly conserved region which partially fulfills the criteria of a PKC site [Brook et al, ]. The previously published studies by Yang et al [] utilizing human skin fibroblasts also reported this same phosphorylation site, while also revealing an additional phosphorylation site at Ser‐425.…”
Section: Hr Structure/function Studiesmentioning
confidence: 73%
“…Our results demonstrate that, in fact, HR selectively binds to a p53 response element (p53RE) of the form 5′‐AGACATGCCTAGACATGCCT‐3′ (the p53 binding core motifs are underlined), but not to response elements for NF‐kB, TCF4, or Sp1. This in vitro finding was confirmed in intact HEK293 and U87 cells using chromatin immunoprecipitation (ChIP) and primers for a portion of the GADD45α promoter containing a p53RE with the sequence 5′‐GAACATGTCT‐AAGCATGCTG‐3′ [Brook et al, ]. Taken together, these results suggest that direct DNA binding by HR may represent, at least in part, a mechanism by which HR modulates target genes for p53.…”
Section: Hr Structure/function Studiesmentioning
confidence: 79%
See 1 more Smart Citation
“…Our previous work demonstrated that HR protein binds to p53RE elements associated with several p53REgulated genes (eg, GADD45A and CDKN1A ) . Herein, we extend these findings to show that HR can modulate the p53 target genes PUMA , GADD45A , and CDKN1A as well as protein levels of other p53 downstream effectors including Survivin and Stathmin 1.…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence showing that HR interacts with HDACs, which partly accounts for its role in transcriptional repression ( 87 , 110-112 ). A recent study has shown that HR recognizes and binds to TP53-response elements, therefore regulating several key TP53 target genes ( PUMA , GADD45A , CDKN1A ) and downstream effectors ( BIRC5 and STMN1 ) ( 109 , 113 ). These findings suggest a possible crosstalk between HR and p53 tumor-suppressor activities.…”
Section: Transcriptional Regulation By Hairlessmentioning
confidence: 99%